The role of scientific research in achieving economic development Applied to White Nile state- Sudan (2015- 2018) - Mohamed, Mahdi Abdalla; Mohamed, Musa Abdalla (Journal of Economic, Administrative and Legal Sciences, 2020)
The study is focusing on the factors which are leading to know the weakness link between the scientific research and economic development in the White Nile state. The important target of the study is to determinate the role of scientific research in the economic development. The study dependence on the statistical analysis method, historical and descriptive method. It aims to collect information related to the problem. The most important result of the study that state has significant savings in production. The most important recommendations of the study the necessity of using scientific research to achieve economic development.
Keywords: scientific research; economic development; local development; White Nile state